Serum urea and serum creatinine in the evaluation of renal functions in children and adults - J. Ahmad, Akram; H. Othman, Lika (Tikrit Journal of Pharmaceutical Sciences, 2023)
The study focused on comparing the biochemical data analysis of serum urea and creatinine levels. Two age groups were selected for the study, children (mean age 5.78 ± 2.50) age and adults (mean age 44,73 ± 14.19). The biochemical data analysis was conducted to compare the first group (27 childs with renal impairment against 31 normal controls) and the second group (44 adults with renal dysfunction compared with 32 normal controls). The results of the data analysis shows that serum urea seems to be a better index in children for renal function while serum creatinine gives a more sensitive indication of renal dysfunction in adults due to effect of diet and other factors on renal function in adults while the skeletal mass, affect the s. creatinine in children due to skeletal muscle mass, although this findings is not statistically significant.